The growth of suicide ideation, plan and attempt among young adults in the Mexico City metropolitan area. (15th August 2016) - Borges, G.; Benjet, C.; Orozco, R.; Medina-Mora, M-E.
Abstract : Aims: Low and middle income countries share a heavy burden of suicide with about three in every four suicides occurring in these countries. Mexico has witnessed a growing trend in suicide deaths; if this trend is not simply a reflection of better reporting of suicide on death certificates, then this increase should logically be accompanied by an increasing trend in suicide ideation, plan and attempts, but we lack information on the trends for suicide ideation, plan and attempt for this period. We therefore aim to report changes for suicidal behaviour for the period 2001–2013 in the Mexico City Metropolitan Area. Method: Using two cross-sectional surveys conducted in Mexico in 2001 and 2013, we report the lifetime and 12-month prevalence of suicide ideation, plan and attempt and changes in treatment for these problems among respondents aged 19–26 living in the Mexico City Metropolitan Area 12 years apart. To estimate the changes in prevalence for each outcome, we used generalised linear models to calculate prevalence ratios (PR; the prevalence rate in the exposed (year 2013) divided by the prevalence rate in the unexposed (year 2001–2002), adjusting for sociodemographic variables. Results: While increases in the prevalence are noted everywhere, statistical comparisons only found differences for lifetime ideation (PR = 3.1; 95% CI = 1.7–5.8) and a borderline difference for suicide attempt (PR = 2.2; 95% CI = 1.0–4.9). No attempt within the last 12-months was reported in 2001, but the prevalence in 2013 reached 1.5% (18 cases). While PRs for 12-month prevalence were all above the null, none reached statistically significant differences. During this 12-year period, the distribution of mental disorders and the use of services for mental disorders among suicide ideators, planners and attempters did not change in any noticeable way. Conclusions: The limitations of our data are the small number of participants in the 2001 survey, the low follow-up rate for the survey in 2013 and that while representative from one city it does not represent the whole country. These findings suggest that suicide ideation and attempt may have increased during this 12-year period in the Mexico City metropolitan area, but this increase did not lead to more use of mental health care services. This information, coupled with the long-term trend of increasing suicide death rates in the country, draw a worrisome and neglected scenario for our youth in this region. Urgent measures, following the recent WHO guidelines for suicide prevention, must not be postponed.